Radiological Modalities for the Assessment of Fetal Growth Restriction: A Comprehensive Review - Abdulqader, shaymaa; Nori, Wassan; Akram, Nabeeha; Al-Kinani , Mortadha (AL-Kindy College Medical Journal, 2024)
Fetal growth restriction is a significant contributor to fetal morbidity and mortality. In addition, there are heightened maternal risks associated with surgical operations and their accompanying dangers. Monitoring fetal development is a crucial objective of prenatal care and effective methods for early diagnosis of Fetal growth restriction, allowing prompt management and timely intervention to improve the outcomes. Screening for Fetal growth restriction can be achieved via many modalities; it can be medical, biochemical, or radiological. Some recommended combining more than one for better outcomes. Currently, there is inconsistency about the best method of Fetal growth restriction screening. In this review, a comprehensive evaluation of the current radiological methods used for Fetal growth restriction, including serial growth scan, Doppler velocimetry, and biophysical profile is offered. Limitations, and potential enhancements area were specifically analyzing the effectiveness. Moreover, recently developed experimental radiological techniques were presented and how to integrate them into practice to enhance follow-up performance and results.